Measurement of the production and elliptic flow of (anti)nuclei in Xe-Xe collisions at sNN =5.44 TeV - Acharya, S.; Basu, S. ; 0000-0003-0687-8124; Christiansen, P.; Hansen, J. ; 0009-0008-4642-7807; Iversen, K.E. ; 0000-0001-6533-4085; Matonoha, O.; Nepeivoda, R. ; 0000-0001-6412-7981; Ohlson, A.; Silvermyr, D. ; 0000-0002-0526-5791; Staa, J.; Zurlo, N. (Physical Review C, 2024)
Measurements of (anti)deuteron and (anti)He3 production in the rapidity range |y|